Controversy of Criminal Sanctions Against Narcotics Abuser in Act No. 35 of 2009 - Bambang Rudi Hartoko; Umar Ma’ruf (Jurnal Daulat Hukum, 2018)
Abuse of narcotics in Indonesia tends to increase. Its effects, not only harm themselves but also the perpetrators of the surrounding environment. On the one hand, drug abusers are the ones who need to be helped to all treatment, but on the other hand, the public and law enforcement thought early abusers are criminals who should be punished. As a legal basis in the eradication of narcotics, Act No. 35 of 2009, there are still concerns about the notion of juridical criminal narcotics, which are related to the sanctions that can be imposed by the judge, especially for sanctions in the form of rehabilitation measures.Keywords: Criminal Sanctions; Abusers; Narcotics.